Utilização do sistema de insensibilização elétrico no abate de tambaqui (Colossoma macropomum) e suas interações no bem-estar e qualidade tecnológica da carne - Carvalho, Luciana Menezes de (2016)
This study examined the effects produced by different methods of stunning / slaughter of tambaqui (Colossoma macropoum), most produced native fish in Brazil. The Tambaqui fish (average weight 1.835 kg ± 428,4g) were subjected to the following stunning methods: hypothermia (Treatment 1) in water and ice at a ratio of 1: 1 to 3.4 ° C for 10 minutes; electronarcosis by AC current intensity of 50 volts for 15 seconds (50V / 15s) (Treatment 2), and electronarcosis 50V / 15s followed by hypothermia in ice water for 10 minutes (Treatment 3). It is concluded that using electronarcosis 50V / 15s proved inefficient both stunning and on meat quality. The rigor mortis in the T1 settled later (21.9% ± 21.85 after 3 hours post-mortem and 73.76 ± 30.98% after 6 hours post-mortem), which is favorable for the handling process in industries however the pH found after 24 hours (6.81 ± 0.19) in this method demonstrates a shorter shelf life time in addition to high stress, once the animal struggles and dies by asphyxiation. The combination of the electrical stunning method at 50V / 15s followed by termonarcose in ice water showed the lowest responses to stress with good meat quality.